Transcriptome analysis reveals differential effects of beta-cypermethrin and fipronil insecticides on detoxification mechanisms in Solenopsis invicta - Siddiqui, Junaid Ali; Luo, Yuanyuan; Sheikh, Umer Ayyaz Aslam; Bamisile, Bamisope Steve; Khan, Muhammad Musa; Imran, Muhammad; Hafeez, Muhammad; Ghani, Muhammad Imran; Lei, Nie; Xu, Yijuan (Frontiers in Physiology, 2022)
Insecticide resistance poses many challenges in insect pest control, particularly in the control of destructive pests such as red imported fire ants (Solenopsis invicta). In recent years, beta-cypermethrin and fipronil have been extensively used to manage invasive ants, but their effects on resistance development in S. invicta are still unknown. To investigate resistance development, S. invicta was collected from populations in five different cities in Guangdong, China. The results showed 105.71- and 2.98-fold higher resistance against fipronil and beta-cypermethrin, respectively, in the Guangzhou population. The enzymatic activities of acetylcholinesterase, carboxylases, and glutathione S-transferases significantly increased with increasing beta-cypermethrin and fipronil concentrations. Transcriptomic analysis revealed 117 differentially expressed genes (DEGs) in the BC-ck vs. BC-30 treatments (39 upregulated and 78 downregulated), 109 DEGs in F-ck vs. F-30 (33 upregulated and 76 downregulated), and 499 DEGs in BC-30 vs. F-30 (312 upregulated and 187 downregulated). Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that DEGs associated with insecticide resistance were significantly enriched in metabolic pathways, the AMPK signaling pathway, the insulin signaling pathway, carbon metabolism, peroxisomes, fatty acid metabolism, drug metabolism enzymes and the metabolism of xenobiotics by cytochrome P450. Furthermore, we found that DEGs important for insecticide detoxification pathways were differentially regulated under both insecticide treatments in S. invicta. Comprehensive transcriptomic data confirmed that detoxification enzymes play a significant role in insecticide detoxification and resistance development in S. invicta in Guangdong Province. Numerous identified insecticide-related genes, GO terms, and KEGG pathways indicated the resistance of S. invicta workers to both insecticides. Importantly, this transcriptome profile variability serves as a starting point for future research on insecticide risk evaluation and the molecular mechanism of insecticide detoxification in invasive red imported fire ants.